2016
DOI: 10.4103/0974-8490.178648
|View full text |Cite
|
Sign up to set email alerts
|

Extracts from Flammulina velutipes inhibit the adhesion of pathogenic fungi to epithelial cells

Abstract: Background:Recently, extracts from natural sources have been tested for their antifungal properties. In this aspect, Flammulina velutipes extracts possess a significant amount of branch-chained carbohydrates with mannose moieties that, hypothetically, can reduce the adhesion.Objective:In this study, we assessed the capacity of extracts from F. velutipes (wild-type AQF-1 and ATCC 34574 as the reference strain) to inhibit the adhesion of S. schenkii and C. albicans to epithelial cells.Materials and Methods:The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…F. velutipes also partially replaced the other three plant pathogenic fungi tested namely Fusarium oxysporum, Pestalotiopsis funerea and Fusarium culmurum LM2091 (Borhani et al, 2011). Recently, a study demonstrated that the extract from F. velutipes exhibited inhibitory activity toward the adhesion of pathogenic fungi ( Sporothrix schenckii and Candida albicans ) to epithelial cells (L929 cell line) (Kashina et al, 2016). …”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…F. velutipes also partially replaced the other three plant pathogenic fungi tested namely Fusarium oxysporum, Pestalotiopsis funerea and Fusarium culmurum LM2091 (Borhani et al, 2011). Recently, a study demonstrated that the extract from F. velutipes exhibited inhibitory activity toward the adhesion of pathogenic fungi ( Sporothrix schenckii and Candida albicans ) to epithelial cells (L929 cell line) (Kashina et al, 2016). …”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…Also discovered to have antimicrobial properties against Gram-positive and Gram-negative bacteria such as Bacillus subtilis, Bacillus pumilus, Staphylococcus aureus, and Pseudomonas aeruginosa was a methanol extract of natural Flammulina velutipes fruiting body from Macedonia. A dual culture in vitro experiment that measured the adversarial interaction between the mushroom and the pathogens was used to study the pharmacological activity of Flammulina velutipes over plant pathogens [43,44].…”
Section: Relevance Of Edible Mushrooms As a Successful Antimicrobial ...mentioning
confidence: 99%